Penyidikan Tindak Pidana Pencabulan Yang Pelakunya Warga Negara Asing Asal Pakistan Terhadap Anak Di Polda Sumbar (Laporan Polisi Nomor : LP/B/446/XII/SPKT/POLDA Sumatera Barat) - Oktoriny, Fitra; Nur’aini, Mayang (Normative Jurnal Ilmiah Hukum, 2023)
The territorial principle or territoriality principle is a principle that considers that criminal law in Indonesia applies within the territory of the Republic of Indonesia for anyone who commits a criminal act and this principle is confirmed in Article 2 of the Criminal Code. The formulation of the problem in this research is: How is the investigation of a criminal act of sexual abuse involving a foreign citizen from Pakistan against a child at the West Sumatra Regional Police (Police Report Number: LP/B/446/XII/2021/SPKT/West Sumatra Regional Police)? What are the obstacles in investigating criminal acts of sexual abuse involving foreign nationals from Pakistan against children at the West Sumatra Regional Police (Police Report Number: LP/B/446/XII/2021/SPKT/West Sumatra Regional Police)? How are efforts to overcome obstacles in investigating criminal acts of sexual abuse involving foreign citizens from Pakistan against children at the West Sumatra Regional Police (Police Report Number: LP/B/446/XII/2021/SPKT/West Sumatra Regional Police)? The problem approach used in this research is a sociological juridical approach, namely looking at facts in the field and linking them to applicable legal regulations. The results of the research are the implementation of an investigation into a criminal act of sexual abuse involving a foreign citizen from Pakistan against a child at the West Sumatra Regional Police (police report number: LP/B/446/XII/2021/SPKT/West Sumatra Regional Police) with a report from the public to the PPA Unit West Sumatra Regional Police, after that the police conducted an investigation by investigators, then the investigation turned into an investigation, after finding the perpetrator the investigators made an arrest, then investigators carried out a search, confiscation and detention of the suspect in the West Sumatra Regional Police Detention Center for 20 days plus 40 days by the Sumatra High Prosecutor's Office West, then investigators carried out an examination, and prepared a BAP which was then handed over to the prosecutor. Obstacles in investigating criminal acts of sexual abuse involving foreign citizens from Pakistan against children at the West Sumatra Regional Police (police report number: LP/B/446/XII/2021/SPKT/West Sumatra Regional Police) are the lack of personnel, case files being returned to investigators because incomplete (P19), there is limited ability in foreign languages ??and it is difficult to ask the victim for information. Efforts to overcome obstacles in investigating criminal acts of sexual abuse involving foreign citizens from Pakistan against children at the West Sumatra Regional Police (police report number: LP/B/446/XII/2021/SPKT/West Sumatra Regional Police) include increasing the number of personnel, conducting a review of case files, bringing in language translators from the cultural language section at Andalas University and approaching children as victims.